Understanding Holistic View And Complexities In Big Data Analytics And Business Intelligence (BI) Towards Establishing Strategic Performance Management:A Case Study - Mohamad, Abdul Karim; Jayakrishnan, Mailasan; Mohd Yusof, Mokhtar (American Scientific Publishers, 2018)
We explore the contradictory pressures and features of holistic view in an organization that creates data value on organizational strategic performance using big data analytics and business intelligence (BI) engine within different conceptual frameworks and their impact on strategy development and implementation for strategic performance management.Big data analytics and BI are stressed due to the importance in enabling organizations to deriving better knowledge creation and decision making.Emerging knowledge from structuring big data and using BI together with observing MIT90s,McKinsey seven (7) S’s framework and survey findings are used as the baseline information framework for the formulation and implementation of BI and big data analytics towards designing strategic performance management for an organization.This conceptual framework relates the current big data analytics and BI stages in strategies adoption and implementation via displaying the organizational performance indicator.The outcome will be a design of a strategic performance framework for a typical strategic application.